Corrosion Inhibition studies of poly (N-tertamylacrylamide -co- N-phenyl acrylamide) copolymers by EIS and PDP methods - Kayalvizhy, E.; Hidayah, Euis Nurul; Pazhanisamy, P. (UPN Veteran Jatim, 2022)
Herein, we reported the synthesis and corrosion inhibition studies of poly (N-tert- amylacrylamide-co- N-phenyl acrylamide) copolymers. The copolymers are synthesized by free radical polymerization using NTA and NPAM monomers . The synthesized copolymers are subjected to corrosion inhibition behavior by EIS and PDP methods. Both the methods showed same results of 85.0 percentage of inhibition.